Effect of Saffron Extract, Astaxanthin, and Carnosic Acid on the Levels of Matrix Metalloproteinase-9 and on Body Weight Changes in Arthritis Experiments - Chrastina M; Póništ S; Dráfi F; Švík K; Khademnematolahi S; Pružinská K; Tchorbanov A; Bauerová K (Sciendo, 2023)
The aim of this study was to explore the potential effect of natural compounds and their combination with methotrexate (M) on levels of matrix metalloproteinase-9 (MMP-9) as a key biochemical parameter in rat adjuvant arthritis. Further change of body weight was selected as one of clinical parameters monitored in this animal model.